2012
DOI: 10.1111/bjd.12035
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of occupational irritant contact dermatitis of the hands in relation to filaggrin genotype status and atopy

Abstract: SummaryBackground Filaggrin loss-of-function mutations and atopy may alter the clinical course of irritant contact dermatitis (ICD). Objective To investigate the clinical course of patients with occupational ICD according to loss-of-function mutations in the filaggrin gene (FLG) and atopy. Methods In a prospective cohort study, the clinical course, use of topical corticosteroids, sick leave, recovery rate and job continuation were investigated in 459 inpatients treated for occupational ICD of the hands. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
2
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 32 publications
1
45
2
6
Order By: Relevance
“…Individuals with atopy are a special risk population for occupational irritant contact dermatitis (20). It is known that irritant contact dermatitis is slightly more frequent than allergic contact dermatitis in textile industry (12)(13)16).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with atopy are a special risk population for occupational irritant contact dermatitis (20). It is known that irritant contact dermatitis is slightly more frequent than allergic contact dermatitis in textile industry (12)(13)16).…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, it could be suggested that sex (female), atopy, and wet work should be considered as markers of poor prognosis primarily for ICD. Wet work is known as a highly important occupational and non-occupational skin irritant and is performed mainly by female workers [3], while atopy in the form of childhood or adult atopic eczema or some other atopic disease is undoubtedly the most important independent risk factor in the development of ICD [4,10,30]. It could be stated that predictors of ACD prognosis have not yet been clearly defined, but there is agreement about the influence and interactions of genetic and environmental factors on the development and course of ACD [1,22], with a thus far more clearly presented influence of environmental factors [3,31].…”
Section: Discussionmentioning
confidence: 99%
“…However, the influence of these gene polymorphisms has not yet been clearly established, and the impact of FLG mutations has been shown for the development of nickel ACD [7,8]. Atopy, defined as a genetically defined tendency toward the development of IgE-mediated immune reactions to common environmental allergens with allergic rhinitis, allergic asthma or atopic dermatitis as related clinical phenotypes [9], is clearly presented as the most important risk factor in the development of irritant contact dermatitis (ICD) [4,10]. However, the impact of atopy on the development and course of CS and ACD is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Eldiven kullanımı ile egzamaların yerleşim yerleri, duyarlanılan alerjenler ve atopi öyküsü arasında ilişki bulunamadı. Eldiven kullanan hastaların yaş ortalaması (34), kullanmayanlardan (41) daha düşüktü (p<0,05), yiyecek sektörü çalışanlarının eldiven kullanma oranı diğer gruplardan yüksekti (p=0,03). Eldiven kullanım oranları Grafik 1' de özetlendi.…”
Section: Gereç Ve Yöntemunclassified
“…Sorgulanan hasta sayısı az olmakla beraber çalışmamızda 19 irritan MKD'li hastanın 7'sinde atopi öyküsü saptanmıştır. Atopi varlığının irritan MKD'li hastalarda tedaviye dirence neden olduğu, daha fazla kortikosteroid kullanımı ve işgücü kaybıyla ilişkili olduğu gösterilmiştir 34 . Tedavi sırasında atopi sorgulanması ve bu hasta grubuna özel ilgi gösterilmesi tedavi başarısı yüzdesini arttıracaktır.…”
Section: Grafikunclassified